Novel mutations in actionable breast cancer genes by targeted sequencing in an ethnically homogenous cohort - Akter, Hosneara (BMC Med Genet, 2019)
BACKGROUND: Genetic testing is becoming an essential tool for breast cancer (BC) diagnosis and treatment pathway, and particularly important for early detection and cancer prevention. The purpose of this study was to explore the diagnostic yield of targeted sequencing of the high priority BC genes. METHODS: We have utilized a cost-effective targeted sequencing approach of high priority actionable BC genes (BRCA1, BRCA2, ERBB2 and TP53) in a homogeneous patient cohort from Bangladesh (n = 52) by using tumor and blood samples. RESULTS: Blood derived targeted sequencing revealed 25.58% (11/43) clinically relevant mutations (both pathogenic and variants of uncertain significance (VUS)), with 13.95% (6/43) of samples carrying a pathogenic mutations. We have identified and validated five novel pathogenic germline mutations in this cohort, comprising of two frameshift deletions in BRCA2, and missense mutations in BRCA1, BRCA2 and ERBB2 gene respectively. Furthermore, we have identified three pathogenic mutations and a VUS within three tumor samples, including a sample carrying pathogenic mutations impacting both TP53 (c.322dupG; a novel frameshift insertion) and BRCA1 genes (c.116G > A). 22% of tissue samples had a clinically relevant TP53 mutation. Although the cohort is small, we have found pathogenic mutations to be enriched in BRCA2 (9.30%, 4/43) compare to BRCA1 (4.65%, 2/43). The frequency of germline VUS mutations found to be similar in both BRCA1 (4.65%; 2/43) and BRCA2 (4.65%; 2/43) compared to ERBB2 (2.32%; 1/43). CONCLUSIONS: This is the first genetic study of BC predisposition genes in this population, implies that genetic screening through targeted sequencing can detect clinically significant and actionable BC-relevant mutations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12881-019-0881-0) contains supplementary material, which is available to authorized users.